Erfaringer med færøsk purisme i 130 år - Jacobsen, Jógvan í Lon (Studier i Nordisk, 2026)
The article discusses experiences of a puristic language policy in the Faroe Islands through the last 130 years. In the late 1880s, Faroese purism was launched at the same time as the Faroese written language was increasingly used in the new Faroese newspapers, translations of literature, technical language, etc. During the last 130 years the Faroese lexicon has increased considerably with a many synonyms of foreign words and their Faroese counterparts. The lexicon has in- creased because puristic neologisms are not able to replace all import words. Instead of a renewal of the Faroese lexicon, the result is an increase in synonyms. Another consequence of purism is a growing difference between written and spoken language. This difference has increased during the period as a direct consequence of purism. The large gap between spoken and written Faroese has resulted in a kind of diglossia. The empirical material is taken from a database of spoken Faroese, two text corpora, a news programme in Faroese television, and an illustration of a car with associated words in the Faroese monolingual dictionary.